Penggandaan dan Pengumuman Karya Cipta E-Book Berdasarkan Prinsip Fair Use Ditinjau dari Hukum Positif - Raden Radisa Difa Devina; Tatty Ramli (UNISBA Press, 2022)
Abstract. Technological developments certainly open up opportunities for the book industry to find new ways to market their products, but on the one hand, the possibility of copyright infringement is even greater because of the ease with which it can be duplicated. According to Article 9 Paragraph (2) UUHC, everyone who want to reproduce and publish a work must obtain permission from the Author/Copyright Holder. In fact, there are still many parties who reproduce and publish e-books without permission on the grounds that their actions are carried out for educational purposes. Based on these problems, this study will examine the regulation regarding the duplication and announcement of copyrighted works e-book and the limits of provisions fair use incopying e-book that do not harm the Creator in terms of positive law and its development. The research method used is a normative juridical approach using descriptive analysis research specifications, data collection techniques are library research using secondary data sources consisting of primary, secondary, and tertiary legal materials, and using qualitative data analysis methods. The results of this study are: according to Article 40 Paragraph (1) letter n, e-books are protected works, so the provisions regarding the reproduction and announcement of works regulated in UUHC also apply to e-books. In addition to duplicating e-books for reasons of fair use and fulfilling the requirements, the actions are categorized as copyright infringement. Reproduction of e-books based on theprinciple fair use has limitations that must be considered, namely not harming the legitimate interests of the Author. The regulation fair use in UUHC does not provide clear parameters regarding the extent to which the limits are not detrimental to the Creator, thus giving rise to multiple interpretations in society. Abstrak. Perkembangan teknologi membuka peluang bagi industri perbukuan untuk menemukan cara baru dalam memasarkan produknya, namun kemungkinan terjadinya pelanggaran hak cipta pun semakin besar karena kemudahannya untuk digandakan. Menurut Pasal 9 Ayat (2) UUHC, setiap orang yang ingin melaksanakan penggandaan dan pengumuman ciptaan wajib mendapatkan izin Pencipta/Pemegang Hak Cipta. Pada faktanya, masih banyak pihak yang melakukan penggandaan dan pengumuman e-book tanpa izin dengan alasan bahwa perbuatannya dilakukan untuk tujuan pendidikan sehingga tidak dikategorikan sebagai pelanggaran hak cipta. Berdasarkan permasalahan tersebut, penelitian ini akan mengkaji tentang pengaturan mengenai penggandaan dan pengumuman karya cipta e-book serta batasan ketentuan fair use dalam penggandaan e-book yang tidak merugikan Pencipta ditinjau dari hukum positif. Metode penelitian yang digunakan yaitu metode pendekatan yuridis normatif dengan menggunakan spesifikasi penelitian deskriptif analisis, Teknik pengumpulan data yaitu penelitian kepustakaan dengan menggunakan sumber data sekunder, serta menggunakan metode analisis data kualitatif. Hasil dari penelitian ini adalah: menurut Pasal 40 Ayat (1) huruf n, e-book merupakan ciptaan yang dilindungi, sehingga ketentuan penggandaan dan pengumuman yang diatur dalam UUHC berlaku juga untuk e-book. Selain penggandaan yang dilakukan dengan alasan fair use dan memenuhi suarat-syaratnya maka tindakannya dikategorikan sebagai pelanggaran hak cipta, Penggandaan e-book berdasarkan prinsip fair use memiliki batasan yang harus diperhatikan, yaitu tidak boleh merugikan kepentingan yang wajar dari Pencipta. Pengaturan fair use dalam UUHC tidak memberikan parameter yang jelas mengenai sejauh mana batasan yang tidak merugikan Pencipta, sehingga menimbulkan multitafsir dalam masyarakat.